Concussions in female athletes: Practical applications for the strength and conditioning expert. - Craig, D. I.; Vogel, T. (Strength and Conditioning Journal, 2020)
With the significant increase in concussion research and focus in the media, it is important for strength and conditioning coaches and medical experts to be clear on sex differences between how female and male concussed athletes may experience a concussion. To that end, this article offers a review of this current research, along with practical applications of the research for coaches and clinicians who work with female athletes. How should we be working with concussed female athletes specifically to assure their optimal recovery and future brain health?